2017
DOI: 10.1080/10447318.2017.1403220
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Technology Acceptance Model with the Inclusion of Trust, Social Influence, and Health Valuation to Determine the Predictors of German Users’ Willingness to Continue using a Fitness App: A Structural Equation Modeling Approach

Abstract: According to one market research, fitness or running apps are hugely popular in Germany. Such a trend prompts the question concerning the factors influencing German users' intention to continue using a specific fitness app. To address the research question, the expanded Technology Acceptance Model (with the addition of trust, social influence, and health valuation) was tested with 476 German users of fitness apps. Structural equation modeling results reveal that respondents' intention to continue using a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
257
6
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(296 citation statements)
references
References 81 publications
(92 reference statements)
27
257
6
6
Order By: Relevance
“…Regarding the exchange of personal data, Shin [47] was able to confirm a positive correlation between trust and attitude towards using social network sites. In the context of fitness apps, Beldad and Hegner [4] already confirmed a positive relationship between trust in the app developer and perceived usefulness, which is correlated to an individual's attitude according to the TAM. Thus, we propose the following hypothesis:…”
Section: Hypothesesmentioning
confidence: 86%
“…Regarding the exchange of personal data, Shin [47] was able to confirm a positive correlation between trust and attitude towards using social network sites. In the context of fitness apps, Beldad and Hegner [4] already confirmed a positive relationship between trust in the app developer and perceived usefulness, which is correlated to an individual's attitude according to the TAM. Thus, we propose the following hypothesis:…”
Section: Hypothesesmentioning
confidence: 86%
“…The present study is one of a few attempts to extend the scope of technology adoption perspective into the context of the continued and actual use of smartphone fitness apps. As previous research on health apps has primarily focused on initial intention to adopt the app [ 81 ], few studies have focused on post-adoption behavior [ 22 ]. Post-adoption behavior of people using smartphone fitness apps is still a new phenomenon; very little is known about it.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of smartphone fitness apps, most of the studies focused on initial app adoption [ 15 ]. One study that used the TAM framework to predict users’ continuance usage [ 22 ] found that perceived usefulness and perceived ease of use, along with social norms, predicted intentions to continue using a particular fitness app among users. It is evident that functionality should be the most prominent quality of fitness apps; hence, our main assumption is that perceived usefulness and perceived ease-of-use affect usage intention and, thus, usage behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis used is SEM is a statistical modeling technique that is cross-sectional, linear, general, and that is usually in the form of causal research. [23]- [25]. Also, conducted exploration using the TOPSIS method to obtain a factor level that significantly affected the use of FinTech services.…”
Section: Introductionmentioning
confidence: 99%